Pendidikan Kesehatan tentang Diabetes Melitus pada Masyarakat RT 3 Kelurahan Curug, Kota Depok - Valentina Dili Ariwati; Martina Martina; Rori Theresia Ka; Kurnia Kusumawati; Hayatun Nufus; Anggi Anggi; Bella Ayu Wandira (LPPM Akbid Harapan Ibu Pekalongan, 2023)
Diabetes mellitus is a metabolic disease caused by insulin disorders, which is characterized by increased blood glucose levels (hyperglycemia). The incidence of diabetes in the world continues to increase. Diabetes can cause blindness, kidney failure, heart attack, stroke, and lower limb amputation. Diabetes can be prevented with a healthy lifestyle such as diet, physical activity, maintaining an ideal body weight, and reducing cigarette consumption. One of the efforts to increase knowledge to prevent diabetes is to provide health education to the society. The purpose of this society service is to increase public knowledge to prevent diabetes. The method used is health education with lectures and discussions about: the definition of DM; signs and symptoms; risk factor; prevention; and complications. The media used is a leaflet. Stages of health education carried out include pre-test, lecture-question and answer, post-test. The results showed that after being given health education, almost all of the participants knew the material provided.